Does having a newborn child affect income diversification opportunities? - Penny, M; Lanata, C; Villar, E; Huttly, S; Suárez, P; Escobal, J (Young Lives (Project), 2005)
The ability of households to diversify their income sources is strongly related to their capacity to cope in times of pressure, such as during economic crises. This is particularly so among the poor, who often do not have adequate resources on which to draw when under such pressures. Households with a newborn child face two additional constraints: the income-generating capability of mothers can be moderately or severely reduced; and households may have to spend more because of the newborn child. Very little is known about whether income diversification strategies are constrained for such households, but such constraints could have serious implications for child well-being at a critical time in the child’s development. This paper describes the income diversification patterns of Peruvian households with young children (aged between 6 and 18 months). Comparisons are made with the overall population in Peru, and with the income diversification patterns of households in the same communities who have no young children. The authors explore links between income diversification strategies, household assets, the external environment and child well-being. Their findings give empirical support for policy or project interventions aimed at increasing income-generating opportunities for Peruvian women with a newborn child.